Cross-neutralization between vaccine and circulating wild-type mumps viruses in Korea. Issue 13 (26th March 2021) - Won, Hyeran; Kim, Ah-Ra; Yoo, Jung-Sik; Chung, Gyung Tae; Kang, Hae Ji; Kim, Su Jin; Kim, Sung Soon; Lee, June-Woo
Abstract: Mumps is a contagious disease caused by the mumps virus. It can be prevented using mumps vaccines, administered as a measles-mumps-rubella (MMR) vaccine. For first and second dose immunization, children aged 12–15 months and 4–6 years have been administered this vaccine since 1997 in Korea. Nevertheless, mumps outbreaks still occur in vaccinated populations worldwide. Hence, immunity against these diseases may be attenuated, or there are antigenic differences between currently available vaccine strains and circulating wild-type viruses. After the introduction of national immunization programs in Korea, mumps cases became sporadic. Viral genotypes F, H, and I have emerged since 1998 whereas the vaccine strains belong to genotype A. Here, we compared the amino acid sequences of the haemagglutinin-neuraminidase (HN) gene from wild-type viruses and the mumps vaccine and measured the cross-neutralization titers between them. We selected the F, H, and I wild-type mumps strains circulating in Korea from 1998 to 2016 and analyzed changes in the amino acid sequence of the protein encoded by the HN gene. We measured mumps virus-specific IgG and rapid focus reduction neutralization test (FRNT) titers in Korean isolates and sera obtained from 50 children aged 1–2 years who had been administered a single dose of MMR vaccine. Analysis of the HN protein sequences disclosed no changes in the glycosylation sites but did reveal 4–5 differences between the Korean isolates and the genotype A vaccine strain in terms of the neutralizing epitope sites on their HN proteins. Post-vaccination FRNT titers were significantly lower against genotypes F, H, and I than they were against genotype A. This finding highlights the possibility of a recurrence of mumps outbreaks in vaccinated populations depending on the degree of genetic conservation of the HN gene. Further research into this issue is needed to prevent the resurgence of mumps.